The Effect of Tax Education, Tax Law, and Taxpayer Awareness on Restaurant Taxpayer Compliance - Mat Juri; Muhammad Abadan Syakura; Omar Dhanny; Angga Kusumah (International Journal of Business and Quality Research, 2026)
This research investigates the influence of tax education, tax law, and tax awareness on the compliance of Restaurant taxpayers in Samarinda City. The study focuses on business taxpayers registered under the Tax on Certain Goods and Services (PBJT) administered by the regional government. A quantitative approach was employed by distributing questionnaires to 75 respondents selected through purposive sampling techniques. The collected data were processed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4 software. The findings reveal that tax education and taxpayer awareness significantly contribute to improving PBJT taxpayer compliance. In contrast, tax law does not demonstrate a significant influence on taxpayer compliance. These results indicate that increasing taxpayers’ understanding and awareness is more effective in encouraging compliance behavior than relying solely on legal enforcement.